COMPARISONAL ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND AFTER THE COMPANY COVID 19 PANDEMIC REGISTERED FOOD AND DRINK ON THE INDONESIA STOCK EXCHANGE - Lila Bisamala; Muafa (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to determine the financial performance of food and beverage companies listed on the Indonesia Stock Exchange in the period before and after covid-19 when viewed from the liquidity ratio, to find out the financial performance of food and beverage companies listed on the Indonesia Stock Exchange in the period before and after covid-19 when viewed from the solvency ratio, liquidity ratio, profitability ratio, activity ratio. The population in this study of Food and Beverage Sector Companies listed on the IDX was 24 companies and a sample from the study was 7 companies with 2 years of observation. The data collection technique used in this study is documentation. The analytical technique used in this study is descriptive analysis with the independent sample T-test different test analysis method to determine hypotheses. The results showed that there was no significant difference between food and beverage companies listed on the Indonesia Stock Exchange before and after covid 19, Debt To Equity Ratio there was no significant difference between food and beverage companies listed on the Indonesia Stock Exchange before and after covid 19, Return On Assets there is no significant distinction between food and beverage companies listed on the Indonesia Stock Exchange before and after covid 19, Inventory Turn Over does not have a significant difference between food and beverage companies listed on the Indonesia Stock Exchange before and after covid 19, Working Capital Turnover there were no significant differences between food and beverage companies listed on the Indonesian Stock Exchange before and after covid 19 and Return On Equity, Debt To Total Asset Ratio, Current Ratio and Inventory Turn Over simultaneously there was no significant difference in Food and Beverage Companies Listed on the Indonesia Stock Exchange.